1995
DOI: 10.1051/jp4:1995214
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Magnetic Properties of Stress-Induced Martensites in Ni-Mn-Ga Alloys

Abstract: The stress-induced transformation of single crystals of Ni-Mn-Ga ferromagnetic Heusler ordered alloys to new martensitic structures has been investigated. The intermartensitic transformations, whenever they occur, were registered during heating by calorimetry, dilatometry and magnetic susceptibility measurement, showing up a step-like strain recovery, small endothermal effects, and an abrupt change of the low-field magnetic susceptibility. During intermartensitic transformations, between modulated and unmodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…This value of parameter κ results in a ∆S mag = 14.3 J/kg K, which corresponds to a Q mag = 4.1 J/g, with T M ≈ 285 K for this alloy. The estimated Q mag is similar to the experimental value of the transformation heat Q ≈ 4.2 J/g reported for this alloy [22,23]. It can be concluded, therefore, that the magnetic subsystem of this alloy is the main contributor to transformation heat and entropy change.…”
Section: Evaluation Of Magnetic and Non-magnetic Contributions To ∆S supporting
confidence: 72%
“…This value of parameter κ results in a ∆S mag = 14.3 J/kg K, which corresponds to a Q mag = 4.1 J/g, with T M ≈ 285 K for this alloy. The estimated Q mag is similar to the experimental value of the transformation heat Q ≈ 4.2 J/g reported for this alloy [22,23]. It can be concluded, therefore, that the magnetic subsystem of this alloy is the main contributor to transformation heat and entropy change.…”
Section: Evaluation Of Magnetic and Non-magnetic Contributions To ∆S supporting
confidence: 72%
“…The lattice constant a 0 in the austenite phase at room temperature is 0.582 nm. On cooling, the cubic phase distorts by a diffusionless martensitic transformation to a lower symmetry martensite phase which can be tetragonal, orthorhombic, or monoclinic [19,20]. The stoichiometric martensitic phase has point group I4/mmm ( Figure 1-2 b), but the more common off-stoichiometry martensites have more complex structures.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…1,[13][14][15] Moreover, it has been experimentally confirmed that the martensitic structures encountered in Ni-Mn-Ga alloys affect their magnetic properties. 16) In this paper emphasis will be given to certain details of the relationship between the crystallographic peculiarities of martensite and its magnetic characteristics. In particular, a possible influence of c/a value on the magnitude of magnetostrain effect for a given magnetic field amplitude will be highlighted.…”
Section: Introductionmentioning
confidence: 99%